Improved fast leakage assessment based on online counting - Zhengguang SHI; Mengce ZHENG; Honggang HU; Nenghai YU (网络与信息安全学报)
Fast leakage assessment (FLA) was proposed in 2017, which made use of the idea of ＆quot;counter＆quot; and significantly improves the computing efficiency.The performance of FLA was analyzed, an online-counting based method was proposed to improve the evaluation flow, and the method was also validated via FPGA implementation.According to the comparisons of experimental results, the proposed method could not only decrease the required memory but also lower the runtime of the evaluation flow.Hence it can improve the evaluation efficiency significantly.